Analisis Perubahan Lingkungan, Sosial dan Ekonomi Pasca Reklamasi Pantai Manado - Kawonal, Shania Chelsie Dalla; Rondonuwu, Dwight Moody; Tilaar, Sony (Universitas Sam Ratulangi, 2024)
Spatial changes in coastal areas have many causal factors, one of which is characterized by changes in sea edge lines.In the case of changes in seashore lines in coastal areas, this affects several aspects, one of which is the human aspect,namely beach reclamation activities. Coastal reclamation is used as an alternative for adding land, where the land inthe reclamation area is in the form of an old land area that is directly connected to new land. Reclamation is definitelyaimed at improving a region, but on the other hand, many things have changed in a positive or negative direction interms of environmental, social and economic aspects for fishermen. This research was conducted to analyzeenvironmental, social and economic changes after the reclamation of the Manado coast. The analytical method used isdescriptive qualitative and analysis of environmental, social and economic changes is carried out through overlay. Theresearch results identified two main things. First, from the characteristics of the coastal area, it is dominated by landfor trade in goods and services and the reclamation area has a coastline length of 10,225 meters. Second, throughoverlay analysis, there are several changes experienced by traditional fishermen, namely the increase in coastal landarea, access to the sea is increasingly difficult. , the unique habits and culture of fishermen are disappearing, incomeis decreasing, causing changes in the livelihoods of fishermen. Keywords: Economy, Environment, Fishermen, Reclamation, Social